2015
DOI: 10.1364/oe.23.030057
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoheater based on NaGdF_4:Yb^3+, Er^3+ upconversion nanoparticles

Abstract: Upconversion nanoparticles (UCNPs) provide an ideal platform for achieving multifunction, such as multimodal imaging, sensing, therapy, etc., mainly by combining with other nanomaterials to construct complicated heterogeneous nanostructures. Multifunctional integration on a simple single-phase structure still is an open question and poses a big challenge. Here we show that small-sized NaGdF(4):Yb(3), Er(3+) UCNPs (~7.5 nm) can simultaneously possess upconversion luminescence (UCL), temperature sensing, paramag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Both UCNPs and BPQDs solutions rose < 10°C within 30 min under the corresponding laser excitation, consistent with several literature reports. 36,55,56 Therefore, our above results confirmed that the thermal effect in the UBAL protocells has three origins: the first is from the UCNPs solution, the second is from BPQDs absorbing the converted visible light to generate extra heat, and the third is from BPQDs excited by an 808 nm laser. Furthermore, the thermal effect of UBAL was derived primarily from the heat absorption of BPQDs.…”
Section: Photoresponse Performance and Selective Recognition Functionsupporting
confidence: 71%
“…Both UCNPs and BPQDs solutions rose < 10°C within 30 min under the corresponding laser excitation, consistent with several literature reports. 36,55,56 Therefore, our above results confirmed that the thermal effect in the UBAL protocells has three origins: the first is from the UCNPs solution, the second is from BPQDs absorbing the converted visible light to generate extra heat, and the third is from BPQDs excited by an 808 nm laser. Furthermore, the thermal effect of UBAL was derived primarily from the heat absorption of BPQDs.…”
Section: Photoresponse Performance and Selective Recognition Functionsupporting
confidence: 71%
“…The thermal effect on the emission intensity cannot be ascribed to eventual particle coalescence or to a modification of the surface induced by thermal damage of the capping ligands since both effects would produce irreversible changes in the UCNPs' emission profiles. Although the thermal emission quenching effects of large nanocrystals and bulk upconverting materials are well known, only recently the anomalous behavior of small‐sized UCNPs was demonstrated in a set of systematic studies performed by Jiang and co‐workers . Initially, these authors suggested that the phonon density of states is modified by quantum confinement reducing the number of available low‐energy modes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several hypotheses have been formulated to explain this intriguing thermal effect, the matter remains an open question . Systematic studies on UCNP emission intensity controlled by a thermal field have already been performed by Li et al and Shao et al These authors showed that the emission intensity is enhanced with the increase of temperature for UCNPs smaller than a critical size of 20–30 nm, whereas emission quenching occurs for larger particles. These effects were used to control the nanoparticles' emission color via modulation of the irradiation laser power, which obviously affected the total intensity of the emissions, or by directly varying the temperature through complex heating systems, involving a copper sample cell and a ceramic plate controlled by a proportional‐integral‐derivative (PID) regulator .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since 2015, it was understood that the thermal effects on the light emission of organic‐capped UCNPs is a size‐dependent phenomenon. Systematic studies on the emission intensity of the particles upon distinct temperatures were performed by Li et al and Shao et al The authors showed that at higher temperatures (e.g., 300–500 K) whereas the emission intensity is enhanced for particles smaller than a critical size (e.g., 20–30 nm), it is quenched for bigger particles. This effect was used to control of NPs' emission color via modulation of the irradiation laser power or directly varying the temperature (through complex heating systems) .…”
Section: Current Trends In Lanthanide‐based Luminescent Thermometersmentioning
confidence: 99%